2000
DOI: 10.1007/s11663-000-0083-2
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial heat transfer and nucleation of steel on metallic substrates

Abstract: A modified levitated drop technique and an immersion technique were used to study the wetting and nucleation behavior of steel melts on a metallic substrate. Thermal histories of the solidifying shell and the substrate were recorded and used to elucidate the mechanisms of interfacial heat transfer and nucleation. The melt/substrate wetting behavior was shown to be controlled by the melt surface tension. The interfacial heat transfer resistance was controlled by the degree of melt/substrate wetting consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 8 publications
(5 reference statements)
0
26
0
Order By: Relevance
“…1,4,6,10) Finally results available in the literature on the effect of melt surface tension have already been mentioned in the introduction. 2,4,5) In this work the final sulfur content in the iron samples cast in a gas atmosphere containing H 2 S was about 100 ppm; by using the expression for the liquidus temperature proposed by Turkdogan,11) T melting ϭ1 537Ϫ73. The sulfur pick-up would then lead to only a 2°C decrease in solidus temperature, i.e.…”
Section: Discussion Of the Experimental Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…1,4,6,10) Finally results available in the literature on the effect of melt surface tension have already been mentioned in the introduction. 2,4,5) In this work the final sulfur content in the iron samples cast in a gas atmosphere containing H 2 S was about 100 ppm; by using the expression for the liquidus temperature proposed by Turkdogan,11) T melting ϭ1 537Ϫ73. The sulfur pick-up would then lead to only a 2°C decrease in solidus temperature, i.e.…”
Section: Discussion Of the Experimental Resultsmentioning
confidence: 86%
“…Examples of this are the results by Phinichka, 4) Strezov et al 2) and Evans et al 5) All of these authors found that, when casting steel in direct contact with a cooling substrate, the heat extraction rates increased with the increase of the concentration of the considered surface-active element (sulfur or tellurium). A higher content of surface active elements leads to a lower melt surface tension, which results in better wetting conditions between the mold and metal and thus better heat transfer conditions.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, the surface tension and contact angles values were taken from other publications and were not measured simultaneously with the heat transfer. Evans and Strezov [26] used a levitation apparatus to melt 0.7 g steel droplets and showed that an increase in the surface tension of steel droplets was associated with a decrease in the maximum heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…There is indirect evidence that this may be the case through the work reported in references [23][24][25][26] but there is clearly a need for more experimental data. The experiments were carried out with aluminum droplets impinging on a copper substrate.…”
Section: Introductionmentioning
confidence: 99%